PENGARUH VERBAL BULLYING TERHADAP KECERDASAN INTERPERSONAL SISWA SD MUHAMMADIYAH IDI TELLO BARU - Ririn Amelia; Ashar; Maisar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the influence of verbal bullying on students’ interpersonal intelligence at SD Muhammadiyah Idi Tello Baru. The research is motivated by the presence of verbal bullying behaviors such as mocking, negative labeling, and degrading remarks among students, which potentially affect their social development. The objective of this study is to describe the phenomenon of verbal bullying and analyze its relationship with students’ interpersonal intelligence. This research employed a quantitative approach with an ex post facto and correlational design. The sample consisted of 19 students selected through a sampling technique, and data were collected using Likert-scale questionnaires measuring verbal bullying and interpersonal intelligence. The instruments were tested for validity and reliability prior to use. Data analysis included descriptive statistics, normality testing, and Pearson Product Moment correlation. The results indicated that most students experienced low levels of interpersonal intelligence and low to moderate levels of verbal bullying. The correlation analysis revealed a very weak relationship between verbal bullying and interpersonal intelligence (r = 0.032; p = 0.898), indicating no significant effect. However, theoretically, verbal bullying still has the potential to negatively influence students’ social abilities. Therefore, preventive efforts are necessary to create a supportive learning environment.